Assessment of genetic variability and association studies for yield related traits in soybean - V. Vasanth1 , K. Anandhi1*, S. Geetha1 , G.Senthilraja2 and P. Meenakshi3 (Electronic Journal of Plant Breeding, 2023)
Soybean is an important legume cum oil seed crop of the country. Generation of information on genetic control of traits and association among them could play a great role in targeted crop improvement. In this study, 76 soybean genotypes including five checks were characterized and evaluated during summer, 2023. The traits namely plant height, number of branches per plant, number of pods per plant, number of clusters per plant and single plant yield showed high GCV and PCV. High heritability and GAM were also observed for the above traits. Traits namely the number of pods per plant, number of branches per plant, number of clusters per plant, number pods per cluster, number of seeds per pod and plant height had significant correlation with yield and direct effects observed to be higher for number of pods per plant and plant height. This study suggested that selection for number of pods per plant, number of branches per plant and number of clusters per plant could be useful to improve the yield and evolve high yielding varieties.